Modifikasi Penggunaan Metode Tanya Jawab Dalam Meningkatkan Efektivitas Pembelajaran Pendidikan Agama Islam Di SMK Favorit Pungging Mojokerto - Munawaroh, Mas'ulil; Muhaimin, Abdul (Universitas Yudharta Pasuruan, 2022)
The use of the question and answer method is not only intended to create direct communication between teachers and students so that there is a direct reciprocal relationship between teachers and students or even students and students, but also makes students have a deep understanding or understanding of the facts they are learning. This study aims to determine how the teacher's efforts to streamline Islamic religious education learning through the question and answer method and the factors that support and inhibit the effectiveness of Islamic religious education learning through the question and answer method at the "FAVORIT" Vocational School Pungging Mojokerto. This qualitative descriptive study with a sample of 39 students resulted in the conclusion that efforts to combine or modify the use of the question and answer method with other methods in Islamic religious education learning activities, questions that are not rote in nature, Supporting factors provide equal opportunities for students who are active and not active, while the inhibiting factor is limited time, students are indifferent to the lesson.